A new species of Olethreutes Hübner, 1822 (Lepidoptera, Tortricidae, Olethreutinae) from Korea, with diagnosis of four allied species - Kim, Jeong-Nam; Bayarsaikhan, Ulziijargal; Lee, Tak-Gi; Cha, Yeong-Bin; Kim, Hanul; Bae, Yang-Seop (Zootaxa, 2025)
A new species of Olethreutes Hübner, 1822, O. palbongensis Kim & Bae, sp. nov. from Korea is described as new to science. We provide diagnostic features of four allied species, O. arcuella (Clerck, 1759), O. captiosana (Falkovitsh, 1960), O. oculata Kim, Byun & Bae, 2022, and O. subtilana (Falkovitsh, 1959), along with a redescription of the female genitalia of O. captiosana. Additionally, illustrations of adults and genitalia are provided for all known species.